2018
DOI: 10.11604/pamj.2018.30.288.16672
|View full text |Cite
|
Sign up to set email alerts
|

Labour pain perception: experiences of Nigerian mothers

Abstract: IntroductionLabour pain perception is influenced by a variety of factors; hence women experience and cope with labour pain differently. This study was designed to assess labour pain perception among parturient.MethodsA cross-sectional study involving 132 pregnant women who had vaginal delivery at two tertiary hospitals in south west Nigeria. A structured questionnaire was administered to women within 24 hours of delivery to record details of labour and delivery. Labour pain perception was assessed using the Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 18 publications
(28 reference statements)
1
18
0
2
Order By: Relevance
“…Mahmood (2016) stated that unfamiliar, crowded and noisy environment of hospitals make childbirth an unpleasant experience [32]. Akadri and Odelola, (2018) stated that environmental factors and the degree of strangeness of the environment (equipment, sound, light and restrictiveness) have a great effect on labor pain [33]. Based on evidence, interactions among physiologic, psychosocial and environmental factors affect women's perceptions of labor pain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood (2016) stated that unfamiliar, crowded and noisy environment of hospitals make childbirth an unpleasant experience [32]. Akadri and Odelola, (2018) stated that environmental factors and the degree of strangeness of the environment (equipment, sound, light and restrictiveness) have a great effect on labor pain [33]. Based on evidence, interactions among physiologic, psychosocial and environmental factors affect women's perceptions of labor pain [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, considered spiritual health as a valuable coping strategy for adapting to pregnancy and childbirth (13). Akadri and Odelola (2018) suggested that religious beliefs may empower women to tolerate the labor pain (33). Mohamadirizi et al (2018) argued that religious-spiritual support can increase selfefficacy among women in child birth (47).…”
Section: Discussionmentioning
confidence: 99%
“…Mahmood (2016) stated that unfamiliar, crowded and noisy environment of hospitals make childbirth an unpleasant experience (32). Akadri and Odelola, (2018) stated that environmental factors and the degree of strangeness of the environment (equipment, sound, light and restrictiveness) have a great effect on labor pain (33).…”
Section: Discussionmentioning
confidence: 99%
“…Tork Zahrani et al (2019) considered spiritual health as a valuable coping strategy for adapting to pregnancy and childbirth (13). Akadri and Odelola (2018) suggested that religious beliefs may empower women to tolerate the labor pain (33). Mohamadirizi et al (2018) argued that religious-spiritual support can increase selfefficacy among women in child birth (47).…”
Section: Discussionmentioning
confidence: 99%